Experimental investigation on the mooring dynamics of the flexible trash intercept net under wave-current combined actions. (15th January 2023) - Xie, Mingxiao; Li, Shan; Mu, Yu; Wei, Yanjie; Xu, Tiaojian; Sun, Zhenxiang; Yuan, Chunguang
Abstract: The flexible trash intercept constructed in the intake channel is an important barrier for coastal power plants to prevent the risk of marine trash intrusion. Experimental tests were carried out to investigate the mooring dynamic response of a typical planar net under various wave-current combinations. Results revealed that under the environment of current only, the total tension of mooring lines presents an exponential relationship with net Reynolds number. Under the wave-current combined actions, the mooring line tension responses simultaneously with instantaneous velocity. Decomposing the wave-current combined velocity into three components including pure current velocity, wave oscillatory velocity and Stokes drift, an empirical expression of the maximum mooring line tension under wave-current combined actions was established. For the spatial distribution, results indicated that the top lines and beam lines bear most of the total tension. The blockage of the net greatly changes the mooring dynamics, that is, the line tension rapidly grows as blocking rate increases. When the blocking rate reaches 50%, the total line tension becomes 4 to 10 times of that without blockage, and the line tension further concentrates in the top lines. Highlights: Experimentally investigated the mooring dynamics of flexible Trash Intercept Net under wave-current combined actions. Proposed a new form of expression between mooring line tension and hydrodynamics considering wave nonlinearity. Discussed the tension spatial distribution of multiple mooring lines under various dynamic conditions. Analyzed the effects caused by net blockage induced by debris.